Polskie reakcje na I rozszerzenie Wspólnot Europejskich o Wielką Brytanię, Danię, Irlandię (1961-1973) - Barabasz, Adam (Rocznik Integracji Europejskiej, 2015)
The primary objective of this paper is to examine the response of the authorities of the Polish People’s Republic to the extending scope and range of European integration in 1961–1973. The following countries applied for EEC membership in this period: the United Kingdom, Ireland and Denmark. The analysis is conducted on the basis of press releases of the Polish Press Agency (PAP) as well as features published in newspapers and magazines (“Trybuna Ludu”, “Polityka”, “Nowe drogi”, “Ideologia i Polityka”), as well as academic periodicals (“Przegląd Międzynarodowy”, “Przegląd Zachodni”).